A Review on Development and Operational Strategy of Fault Current Limiters - S.P. Janani Priyadharshna; T. Venkatesan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Distributed Generation (DG) plays a major role in existing power system. When such distributed generation system is interconnected with micro-grid improves voltage profile, power quality but at the same time results in fault conditions. Among various faults occurring in the power system, short circuit faults are the most predominant case. This results in the increase in flow of the fault current in the line. Also the equipments installed in such a line get damaged internally due to flow of excess fault current. Therefore in order to improve the transient conditions and limit the fault current to a manageable level, a device called Fault Current Limiters (FCLs) are being used in recent trend. This paper reviews about various fault current limiters, their development, characteristics and operating performance in the system. It gives a detailed knowledge about various operations performed by fault current limiters that is compared with other conventional techniques.